Gifted and Talented Students' Perceptions of Media Literacy (Case of Elazig Science and Art Center) - Gomleksiz, Mehmet Nuri; Kan, Ayse Ulku; Oner, Ummuhan (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2012)
Media literacy, which is defined as accessing, analyzing, evaluating and producing media messages in a variety of contexts, has gained importance as media covers every part of our daily life. Individuals are expected to be media literate as well as other kinds of literacy. In this context, the aim of this study is to explore opinions of Science and Art Center students in Elazig toward media literacy. This is a qualitative study and case study design which is one of the qualitative research methods was adopted. Study group of this research includes 11 gifted and talented students (six female-five male) enrolled at Elazig Science and Art Center. Data of the study were collected with an interview form including eight semi-structured questions. Totally 11 high school students were interviewed during study process. Descriptive analysis was utilized to analyze the data. Study results revealed that the students had information about media literacy. They mostly used internet, television and cell phones. The students indicated that they watched serials on television. Google is the most used search engine and they frequently use social forums. They complained about false news and harmful web-sites and indicated that they preferred reliable sites. They used social media to communicate with their friends. They demanded to be informed and to gain auto control to save themselves from the harmful sides of media.
Keywords: Media; media literacy; science and art center; internet; social media